PERBEDAAN JENIS KELAMIN TERHADAP KEPUASAN SISWA TERHADAP PEMBELAJARAN FISIKA ONLINE - Syarkowi, Ahmad; Hamdani, Dedi; Defianti, Aprina (EduFisika: Jurnal Pendidikan Fisika, 2023)
The purpose of this study was to see the level of student satisfaction in carrying out online learning by comparing the perspectives of male and female students. This study used a cross sectional survey research method to 329 students in Bengkulu province consisting of 130 male students and 199 female students. Sampling for this study used a random system. The results showed that the highest satisfaction index for female students was the score they got during their activities with an average score of 4.10, on the contrary, they had the lowest score on the belief that they could study independently without face-to-face, which was the lowest point with a score of 3.07. From the male perspective, they were satisfied with the way to connect the previous learning by the teacher with an average score of 3.94 but the same as female students, most male students were also not sure that they would be able to study online.